Design and Development of A Mobile-Based E-RT Information System in An Effort to Improve Services to Citizens - Pandowo, Hedi; Kusumaningrum, Dian; Tohari, Hamim; Sari, Chanif Kurnia (Journal of Economics and Public Health, 2024)
E-RT is a development of E-Government to improve public services so that people in the surrounding environment can more easily access information. One of the neighborhood Association functions is to create security, order, harmony and comfort in the environment. This security and order can be realized with one rule: guests must report 1 x 24 hours. However, the lack of public awareness of this rule means that the rule is not implemented. So this research aims to develop e-RT applications in the fields of security and order and comfort to increase effectiveness and efficiency, especially in reporting guests who come to the neighborhood Association environment as well as reporting on citizen activities and finances that are transparent and easy to access information. The approach used is qualitative with descriptive methods. The research results are in the form of an e-RT application that can be accessed by residents and neighborhood Association administrators. In this research, application design is based on user needs analysis, where data collection uses the interview method. In visualizing and building application model concepts, this research uses UML. Application testing uses the black box method with initial results containing errors in scenarios three and seven, so the test success is only 80%. After scenarios 3 and 7 have been repaired, especially in the coding part, the application can run 100% according to its needs or function. The conclusion in this research is that E-RT is a faster system for carrying out reporting without being limited by time and distance.